Study of the influence of red ceramic residue, as a partial substitute for the binder or aggregate, in mixed mortars for coating (Research, Society and Development, 2020)
In order to promote a global network of sustainable economic development for developing countries, several countries produced a document with direct guidelines for more sustainable industrial development during the United Nations Conference on Environment and Development in 1992, with emphasis on waste reduction and reuse of by-products. Since the industries that produce ceramic materials are an important branch of the civil construction production chain, it also stands out for being a major generator of waste, the so-called red ceramic residue (RCR). Seeking a more sustainable destination of these by-products, this work aimed to evaluate some possibilities of using the RCR, from the manufacture of sealing bricks, as a substitute for fine aggregate or agglomerate, in mixed mortars with 1: 2: 8 features and 1: 2: 9. The application was evaluated for the mechanical and physical performance of mortars, with contents of 5% and 10% of cement replacement by RCR, and 10%, 15% and 20% of aggregate replacement. The performances of 1: 2: 8 mortars were superior to the 1: 2: 9 traces, both mechanically and in relation to capillary absorption. A different fact occurred when the absorption by immersion and voids index were tested, where the two traits had similar behaviors. The substitutions in the aggregate affected the mortars more mechanically compared to the substitution in the binder, given the greater porosity of the RCR. The substitutions in the binder made the mortars present performances closer to the reference strokes.